(untitled) (Journal of the College of Basic Education, 2022)
This Study aimed to examine the attitudes of public and special education teachers toward behavior modification . The Study population consisted of (182) teachers in Amman and Al-salt . A questionnaire for attitudes was built and applied, after its validity and reliability were verified, to public and special education teachers . T test was used The Study revealed the following results: Both of public and special education teachers have appositive attitudes toward behavior modification. There are significant differences on the attitudes of teachers according to gender , specialization , behavior modification course in behalf of men teachers , special education teachers , teachers who took a course in behavior modification .